2020
DOI: 10.1186/s12888-020-2472-1
|View full text |Cite
|
Sign up to set email alerts
|

Positive and Negative Affect Schedule (PANAS): psychometric properties of the online Spanish version in a clinical sample with emotional disorders

Abstract: Background: The Positive and Negative Affect Schedule (PANAS) is the most widely and frequently used scale to assess positive and negative affect. The PANAS has been validated in several languages, and it has shown excellent psychometric properties in the general population and some clinical samples, such as forensic samples, substance users, and adult women with fibromyalgia. Nevertheless, the psychometric properties of the scale have not yet been examined in clinical samples with anxiety, depressive, and adj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
82
2
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(98 citation statements)
references
References 69 publications
(76 reference statements)
5
82
2
3
Order By: Relevance
“…A higher score indicates higher frequency and/or intensity of positive and negative emotions, while a lower score shows less frequency and/or intensity of the emotions experienced as positive or negative. Both the original validation ( Watson et al, 1988 ) and the Spanish validation ( Díaz et al, 2020 ) showed two clearly differentiated factors (PA and NA) and good psychometric properties. In the current study, the inventory has shown a Cronbach’s alpha of 0.826.…”
Section: Methodsmentioning
confidence: 96%
“…A higher score indicates higher frequency and/or intensity of positive and negative emotions, while a lower score shows less frequency and/or intensity of the emotions experienced as positive or negative. Both the original validation ( Watson et al, 1988 ) and the Spanish validation ( Díaz et al, 2020 ) showed two clearly differentiated factors (PA and NA) and good psychometric properties. In the current study, the inventory has shown a Cronbach’s alpha of 0.826.…”
Section: Methodsmentioning
confidence: 96%
“…A FFECTS are observed dynamic reactions caused by change in our emotions and are directly linked to our mental and physical health [1]. Specifically, the positive affects (PA) and negative affect (NA) give physicians valuable information about mood and anxiety disorders [1]. PA and NA are commonly measured using a self-report questionnaire known as the Positive and Negative Affect Schedule (PANAS) [2].…”
Section: Introductionmentioning
confidence: 99%
“…Affect is regarded as psychological states that refers to personal evaluative feeling for objective things (Diaz-Garcia et al 2020 ). There were two independent dimensions, including positive affect and negative affect (Garcia 2012 ).…”
Section: Introductionmentioning
confidence: 99%